Recurrent seizure-like events are associated with coupled astroglial synchronization - Kékesi, Orsolya (Front Cell Neurosci, 2015)
Increasing evidence suggest that astrocytes significantly modulate neuronal function at the level of the tripartite synapse both in physiological and pathophysiological conditions. The global control of the astrocytic syncytium over neuronal networks, however, is still less recognized. Here we examined astrocytic signaling during epileptiform activity which is generally attributed to large-scale neuronal synchronization. We show that seizure-like events in the low-[Mg(2+)] in vitro epilepsy model initiate massive, long-range astrocytic synchronization which is spatiotemporally coupled to the synchronized neuronal activity reaching its maximum at the electrographic tonic/clonic transition. Cross-correlation analysis of neuronal and astrocytic Ca(2+) signaling demonstrates that high degree of synchronization arises not only among astrocytes, but also between neuronal and astrocyte populations, manifesting in astrocytic seizure-like events. We further show that astrocytic gap junction proteins contribute to astrocytic synchronization since their inhibition by carbenoxolone (CBX) or Cx43 antibody increased the interictal interval and in 41% of slices completely prevented recurrent seizure-like activity. In addition, CBX also induced unsynchronized Ca(2+) transients associated with decreasing incidence of epileptiform discharges afterwards. We propose therefore that local, unsynchronized astrocytic Ca(2+) transients inhibit, while long-range, synchronized Ca(2+) signaling contributes to the propagation of recurrent seizure-like events.